The Effect of Mindfulness-Based Interventions on Tinnitus Distress. A Systematic Review - Rademaker, Maaike M.; Stegeman, Inge; Ho-Kang-You, Krysten E.; Stokroos, Robert J.; Smit, A. L. (Frontiers in Neurology, 2019)
Objectives: With this systematic review we aim to provide an overview of the evidence of the effect of Mindfulness Based Interventions (MBIs) on (1) tinnitus distress and (2) anxiety and/or depression in tinnitus patients. Methods: We conducted a systematic search in PubMed Medline, EMBASE and PsycInfo combining the terms and synonyms of “Tinnitus” and “Mindfulness.” The most recent search was performed on December 4th 2018. We wrote this systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Two independent authors identified studies, assessed the risk of bias and extracted data. Studies were considered eligible if they included adults with tinnitus, performed a protocolled MBI and measured tinnitus distress with validated questionnaires. Studies were appraised with either the Cochrane Risk of Bias tool or the MINORS criteria, depending on their design. Results: The systematic search yielded seven articles (425 patients). Three randomized controlled trials (RCTs), three cohort studies and one comparative controlled trial. Different types of MBIs, including MBCT and MBSR, were assessed with various questionnaires. Two of three RCTs showed a statistically significant decrease in tinnitus distress scores directly after treatment in the mindfulness group compared to the control group. Six of seven studies showed statistically significant decrease in tinnitus distress scores directly after mindfulness therapy. One of three RCTs showed a statistically significant improvement of depression questionnaire scores after MBI compared to the control group directly post treatment. Conclusions: A decrease of tinnitus distress scores in MBIs can be observed directly post-therapy based on moderate to high quality studies. This was found regardless of the heterogeneity of patients, study design, type of MBI and outcome assessment. Two out of three RCTs found clinically relevant decreases in tinnitus distress scores. No effect of MBIs was observed for depression and anxiety in tinnitus patients. Long term effects remain uncertain. Mindfulness may have a place in tinnitus therapy, although the long term effects need to be studied.